A generalization of the strong Fitzpatrick inequality. (3rd June 2017) - Elias, Leonardo M.; Martínez-Legaz, Juan E.
Abstract : We present a generalization of the strong Fitzpatrick inequality in the context of reflexive Banach spaces, involving a twisted bigger conjugate function. We also introduce a related family of gap functions for maximal monotone inclusion problems.